Studi Literatur Potensi Antikanker Pada Daun Ungu (Graptophyllum Pictum (L.) Griff) - Dhiyaa Ramadina Ismaila Putri Djaelani; Indra Topik Maulana; Livia Syafnir (Bandung Conference Series: Pharmacy, 2023)
Abstract. Purple leaves (Graptophyllum pictum (L.) Griff) is a plant that has many properties, including as a diuretic, menstrual stimulant, anti-inflammatory, constipation treatment, hemorrhoids, antireumatic, ulcer treatment, and also as a mild laxative. However, as an anticancer plant, not much research has been done. Therefore, research was carried out with a Systematic Literature Review to obtain more accurate information and also as a reference for researchers in developing new alternative treatments for cancer. This research was conducted to determine the potential of purple leaf (Graptophyllum pictum (L.) Griff) as anticancer, compounds contained in purple leaf (Graptophyllum pictum (L.) Griff) which have potential as anticancer, and also how the mechanism of these compounds in treating cancer. This research was conducted using the Systematic Literature Review method by collecting data through online search engines such as Google Scholar, Garuda Journal, Science Direct, Pubmed, Proquest, Sage Publication, and also Wiley Journal which were then analyzed to obtain 3 appropriate articles. The results showed the presence of phytol compounds, flavonoid which have potential as anticancer compounds in purple leaves (Graptophyllum pictum (L.) Griff). Abstrak. Daun ungu (Graptophyllum pictum (L.) Griff) merupakan salah satu tanaman yang memiliki banyak khasiat, diantaranya ialah sebagai obat diuretik, pelancar haid, antiinflamasi, pengobatan sembelit, ambeien, antirematik, pengobatan bisul, dan juga sebagai pencahar ringan. Namun sebagai tanaman antikanker masih belum banyak dilakukan penelitian. Maka dari itu dilakukan penelitian dengan Systematic Literatur Review untuk memperoleh informasi yang lebih akurat dan juga sebagai referensi bagi peneliti dalam mengembangkan alternatif pengobatan baru untuk kanker. Penelitian ini dilakukan untuk mengetahui potensi daun ungu (Graptophyllum pictum (L.) Griff) sebagai antikanker, senyawa yang terkandung dalam daun ungu (Graptophyllum pictum (L.) Griff) yang memiliki potensi sebagai antikanker, dan juga bagaimana mekanisme dari senyawa tersebut dalam mengatasi kanker. Penelitian ini dilakukan dengan menggunakan metode Systematic Literatur Review dengan melakukan pengambilan data melalui mesin pencari online seperti Google Scholar, Garuda Jurnal, Science Direct, Pubmed, Proquest, Sage Publication, dan juga Wiley Journal yang kemudian dianalisis sehingga didapatkan 3 artikel yang sesuai. Hasil penelitian menunjukkan adanya senyawa fitol, dan flavonoid yang memiliki potensi sebagai senyawa antikanker pada daun ungu (Graptophyllum pictum (L.) Griff).